A Novel Single-Inductor Bipolar-Output DC/DC Boost Converter for OLED Microdisplays - Ingrid Casallas; Robert Urbina; Carlos-Ivan Paez-Rueda; Carlos Adrián Correa-Flórez; José Vuelvas; Manuel Parraga; Abdel-Karim Hay; Arturo Fajardo; Gabriel Perilla (Energies, 2021)
In this paper, a novel SIBO (Single-Inductor Bipolar-Output) DC/DC Boost converter is proposed to power OLED (Organic Light-Emitting Diode) microdisplays. The proposed topology merges a conventional SISO (Single-Inductor Single-Output) DC/DC Boost converter and a switched capacitor inverter to produce a SIBO converter without both the cross-regulation effect and the unbalanced output voltages. Moreover, its control circuit and efficiency are almost the same as the conventional SISO Boost converter. Therefore, the novel converter maintains the power density, the small form factor, and the high efficiency of its conventional counterpart. The proposed converter was analyzed under continuous-conduction mode operation using the moving average operator and charge conservation principle. As a result, the authors proposed an equation set with the main averages and ripples of the circuit variables expressed as analytical functions of the circuit components, the input voltage, and the duty cycle. Both the functionality of the proposed converter and the accuracy of the developed equation set were analyzed by extensive simulations. The simulation performed using ideal components was characterized by a mean absolute percentage error of 0.774% with a standard deviation of 1.566%. These results confirm the high accuracy of the proposed equation set. Furthermore, the non-ideal model simulation confirms the functionality of the proposed converter in “real” operation conditions. Under simulation with non-ideal components, the result statistics were a mean absolute percentage error of 7.36% with a standard deviation of 6.91%. Therefore, the converter design using the proposed ideal model could be a good start point of a converter optimization process based on more complex component models and assisted by computer-aided design tools.